Resistant Yersinia Enterocolitica Peritonitis in a Peritoneal Dialysis Patient - Ozden, Mehmet; Gurel, Ali; Tartar, Ayse Sagmak; Ulu, Ramazan; Dogukan, Ayhan (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2012)
Peritonitis is an important problem of peritoneal dialysis patients. Although Gram (+) bacteria are more frequent, Gram (-) bacteria can rarely be the cause of peritonitis. Yersinia enterocolitica is a Gram (-) enteric bacteria that especially causes gastrointestinal infections via contaminated food intake in immunosuppressive situations such as haemochromatosis, desferroxamine therapy or chronic hepatitis. We report a 51-year-old man who had been undergoing SAPD because of chronic renal failure for 2 years. We evaluated his peritoneal fluid because of symptoms of peritonitis. His peritoneal cellular composition was consistent with peritonitis and after the microbiological culture of the fluid we determined Yersinia enterocolitica as the pathogenic agent. The peritonitis persisted despite the administration of long term combined antibiotherapy and we removed the peritoneal catheter. In conclusion, Yersinia enterocolitica peritonitis is resistant to conventional antibiotic therapy and an indication for catheter removal.
Periton Diyalizi Yapan Olguda DirenÇli Yersinia Enterocolitica Peritoniti
Keywords: Peritoneal dialysis; Peritonitis; Yersinia enterocolitica